SEJARAH PENDIDIKAN ISLAM DI MESIR - Marjuni; Eka Damayanti; Aliman; Sumarni Susilawati (Al Asma: Journal of Islamic Education, 2022)
Islamic education is a very important treasure to explore its ins and outs. The peak of the glory of Islam can be seen from its ability to rule various countries on earth. Including the Egyptian state that was once ruled by the Fathimid Daula. The victory of Islam in Egypt became something pautu to be proud of, because it has become a mecca of knowledge for other countries. Efforts to trace the history of Islamic education can stimulate the condition of Islamic education. The fall of Islam in Egypt became one of the factors driving Islamic scholars to act. Therefore, this paper will describe the history of Islamic education in Egypt. This paper is compiled in accordance with the data obtained in the form of library materials (library research) using descriptive-historical methods. Based on the study in this paper, it was obtained the development of Islamic civilization in Egypt and the decline experienced by Muslims in Egypt to move the hearts of Islamic thinkers.